PELATIHAN PENGUATAN NILAI-NILAI KEMANUSIAAN: ETIKA DAN MORAL BAGI MAHASISWA PRODI TEOLOGI SEKOLAH TINGGI TEOLOGI TABGHA BATAM - Manalu, Nilawaty; Purba, Gomgom; Pasaribu, George Rudi Hartono; Mojumby, Andika Thenri (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The community service themed Training to strengthen human values, ethics, and morals for students of the Theology Study Program at the Tabgha Batam Theological College is an initiative that aims to equip students with deeper insights into social interactions and their moral responsibilities as prospective spiritual leaders. This study uses a qualitative approach with a case study method, which examines the effectiveness of the training program in increasing students' ethical and moral awareness. The training methods used include group discussions, case studies, and involvement in social activities. The results of the study indicate that participation in this training contributed to increasing students' understanding of human values ​​and ethics, as well as their ability to apply them practically in a social context. It was also found that students who were involved in social activities tended to show positive changes in their attitudes and behaviors. Thus, this training program is important to prepare students to face moral challenges in a complex and diverse society.